Pengaruh Struktur Kepemilikan Terhadap Audit Report Lag : Studi Empiris pada Badan Usaha Milik Negara di Indonesia - Muhammad Tipin Natakusuma; Retno Yuni Nur Susilowati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of ownership structure on audit report lag (ARL) in State-Owned Enterprises (SOEs) in Indonesia. The ownership structures studied include managerial ownership, government ownership, and institutional ownership. The research method used is a quantitative approach with multiple linear regression analysis, using secondary data obtained from annual reports and audited financial statements of SOEs listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The results show that managerial ownership has a negative effect on ARL, meaning that the higher the managerial ownership, the faster the audit report completion. Conversely, government ownership has a positive effect on ARL, indicating that the greater the government ownership, the longer the time required to complete the audit report. Institutional ownership also has a negative effect on ARL, indicating that companies with institutional ownership tend to be faster in completing audit reports. This study provides insight into the role of ownership structure in influencing the efficiency of audit report completion time in Indonesian SOEs.